Communication aid requirements of intensive care unit patients with transient speech loss. (1st October 2016) - Mobasheri, Mohammad H.; King, Dominic; Judge, Simon; Arshad, Faizan; Larsen, Marius; Safarfashandi, Zahra; Shah, Hemal; Trepekli, Anna; Trikha, Sanjay; Xylas, Diamantis; Brett, Stephen J.; Darzi, Ara
Abstract: Alert and transiently nonvocal intensive care unit (ICU) patients are dependent on augmentative and alternative communication (AAC). Unfortunately, the literature demonstrates that existent AAC devices have not been widely adopted, and unaided methods are often the primary modalities used despite being insufficient, and frustrating. We present the results of a qualitative semi-structured interview study with 8 ex-ICU patients, 4 ICU patient relatives, and 6 ICU staff, exploring their AAC needs and requirements. Participants identified important AAC hardware, software, and content requirements. Salient factors impacting on AAC adoption in the ICU setting were also highlighted and included the need for staff training and bedside patient assessment. Based on the study results, we propose a series of recommendations regarding the design and implementation of future AAC tools specifically targeted at this group.